Prenatal diagnosis of Jacobsen syndrome with cystic hygroma - Suzuki, Toshifumi; Hayashi, Takashi; Itakura, Atsuo (Indian Journal of Child Health, 2020)
Jacobsen syndrome (JBS) is a rare, contiguous genetic deletion syndrome caused by partial deletion of chromosome 11q. It is difficult to diagnose JBS by ultrasonography during the prenatal period because it has atypical clinical findings. Although nuchal thickening is associated with JBS, cystic hygroma has not been previously reported in conjunction with this syndrome. We describe the first prenatal diagnosis of JBS with cystic hygroma, which was clinically diagnosed at 13 weeks gestation in a Japanese woman, although it had not been detectable at the 11th week of gestation. In addition, a single ventricle fetal heart defect was suspected. Amniocentesis was performed, and G-banded karyotype evaluation revealed 46,XX,del(11)(q23), which is consistent with JBS. Cystic hygroma and congenital heart malformation have been reported to be associated with chromosomal anomalies. The present case indicates that a fetal cystic hygroma without increased nuchal thickness might be associated with JBS.